2021
DOI: 10.1111/jog.14862
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ovarian endometrioma during pregnancy

Abstract: Aim: During pregnancy, the ovarian endometrioma generally decreases in size and occasionally ruptures. We evaluated (1) whether and how ovarian-endometrioma size changes from the first trimester to the postdelivery period, and (2) the type of endometrioma more likely to rupture during pregnancy. Methods: During an 18-year period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018), ultrasound in the first trimester revealed ovarian endometrioma in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In fact, recently, Takami at al. reported a reduced volume of ovarian endometriomas in 68% of cases during pregnancy [56].…”
Section: Discussionmentioning
confidence: 96%
“…In fact, recently, Takami at al. reported a reduced volume of ovarian endometriomas in 68% of cases during pregnancy [56].…”
Section: Discussionmentioning
confidence: 96%
“…According to the literature, the prevalence is less than 3% among women with endometriosis [ 23 ]. This complication can develop spontaneously, there are cases reported during menstruation [ 24 ] and periovulatory stages [ 25 ], but it more often occurs during pregnancy, after abdominal and pelvic trauma [ 26 ]. Also, the risk is higher when the diameter of endometrioma is ≥6cm [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the risk is higher when the diameter of endometrioma is ≥6cm [ 27 ]. Takami et al [ 26 ] reported a 2.8% incidence of the rupture of ovarian endometrioma during pregnancy. They also found enlarging cyst size, adhesion to the adjacent organs and the pressure of rapidly growing uterus being the main risk factors associated with rupture.…”
Section: Discussionmentioning
confidence: 99%
“…This complication most commonly occurs during pregnancy, because of the rapid growth of endometrioma due to hormonal stimulation [ 28 , 29 ]. Clinically, endometrioma rupture may mimic the rupture of a hemorrhagic ovarian cyst with findings ranging from symptoms of inflammation, such as fever, leukocytosis, and elevated c-reactive protein, to acute abdominal pain and signs of hypovolemic shock [ 30 , 31 ].…”
Section: Gynecologic Complicationsmentioning
confidence: 99%